A chiral bowtie Co-based electrocatalyst and preparation method thereof
By adding triethylamine dropwise to a solution containing chiral threonine and treating it by hydrothermal method, a chiral Co nano-breast tie was successfully prepared, which solved the problem of difficult preparation of transition metal chiral inorganic nanomaterials and improved the redox performance.
Patent Information
- Application Number
- CN202410241933.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-04
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-04
AI Technical Summary
The preparation method of transition metal chiral inorganic nanomaterials in the prior art is not clear, and the principle is not clear, making transition metal-based chiral materials more difficult to prepare.
The second solution was obtained by adding triethylamine to the first solution containing chiral threonine, and the second solution was treated by hydrothermal method to obtain a chiral Co nano-breast tie. This method selects chiral threonine and cobalt nitrate hexahydrate as materials, triethylamine adjusts pH, and reacts with hydrothermal method to form chiral structures with different distortion directions.
The problem of difficult to prepare transition metal chiral inorganic nanomaterials was successfully solved. The generated nanobreasts have a stable and uniform chiral structure, which improves redox performance, which is specifically reflected in the reduction of overpotential and the lower Tafel slope.
Smart Images

Figure CN118023534B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a chiral bowtie Co-based electrocatalyst and a preparation method thereof. Background Art
[0002] Chiral structure refers to the inability of an object and its mirror image to completely overlap. Chiral structures are widely distributed in nature, ranging from the various amino acids and spiral DNA molecules that make up living organisms, the spiral structures of plants and animals, to the spiral distribution of cosmic nebulae and celestial bodies in the Milky Way. As an interesting phenomenon, chiral structure has received extensive research attention. Its special chiral structure has unique optical, electrical and biological characteristics. Scientists have been committed to simulating the spiral phenomenon in nature and exploring the mechanism of chiral information transmission and amplification, so as to reveal the origin of life and develop advanced functional materials. In recent years, chiral materials with chiral structures have shown excellent effects in research fields such as biosensors, photoelectric catalysts, and optoelectronic devices.
[0003] The chiral structure was first discovered by Pasteur in tartaric acid crystals, and the role of chiral enantiomers was still unclear. Since the sensational "thalidomide" incident, scientists have conducted more in-depth research on chiral drugs. The differences in the roles of different structures of chiral enantiomers have made people realize the importance of chiral catalysis. Chiral catalysis has been studied by more and more people, and these studies have remained at the chiral molecule stage. In recent years, with the development of nanotechnology, people have developed many exquisite chiral nanomaterials. The excellent physical and chemical properties of nanomaterials based on size effects have stimulated researchers' interest in nanoscale chirality. Through appropriate means, structures similar to chiral molecules can be obtained at the nanoscale. Most of the chiral inorganic nanomaterials that have been studied involve precious metals and metals with relatively large atomic mass, but there are relatively few studies on the construction of transition metal chiral inorganic nanomaterials. This is because the preparation method of transition metal chiral nanomaterials is still unclear and the principle is still unclear.
[0004] Therefore, how to prepare transition metal chiral inorganic nanomaterials has become an urgent problem to be solved. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a chiral bowtie Co-based electrocatalyst and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solutions:
[0006] The present invention provides a method for preparing a chiral bowtie Co-based electrocatalyst, the preparation method comprising:
[0007] adding triethylamine dropwise to the first solution containing chiral threonine to obtain a second solution;
[0008] The second solution is treated by a hydrothermal method, and after the reaction is completed, a chiral Co nano bowtie is obtained.
[0009] In one embodiment of the present invention, triethylamine is added dropwise to a first solution containing chiral threonine to obtain a second solution, comprising:
[0010] adding cobalt nitrate hexahydrate and chiral threonine into deionized water to obtain a first solution;
[0011] Triethylamine was added dropwise to the first solution to obtain a second solution.
[0012] In one embodiment of the present invention, the molar ratio of the cobalt nitrate hexahydrate to the chiral threonine is 5:1 to 1:2.
[0013] In one embodiment of the present invention, triethylamine is added dropwise to the first solution to obtain a second solution, comprising:
[0014] The triethylamine is added dropwise to the first solution, and the mixture is stirred evenly to obtain the second solution.
[0015] In one embodiment of the present invention, the amount of triethylamine added is 1-10 mL.
[0016] In one embodiment of the present invention, the second solution is treated by a hydrothermal method, and after the reaction is completed, a chiral Co nano bow tie is obtained, comprising:
[0017] The second solution is stirred by magnetic stirring, and then the second solution is transferred to a polytetrafluoroethylene liner, and then fixed with a stainless steel jacket. Thereafter, the second solution is subjected to a hydrothermal reaction at a preset temperature to obtain the chiral Co nano bow tie.
[0018] In one embodiment of the present invention, the second solution is subjected to a hydrothermal reaction at a preset temperature to obtain the chiral Co nano bow tie, comprising:
[0019] The second solution is subjected to a hydrothermal reaction at 160° C. to 200° C. for 2 h to 12 h to obtain the chiral Co nano bow tie.
[0020] In one embodiment of the present invention, after the second solution is treated by a hydrothermal method and the chiral Co nano bowtie is obtained after the reaction is completed, the method further comprises:
[0021] The chiral Co nano bow tie is washed with anhydrous ethanol and deionized water in sequence, and then dried to obtain a dried chiral Co nano bow tie.
[0022] The present invention also provides a chiral bowtie Co-based electrocatalyst, wherein the chiral bowtie Co-based electrocatalyst is prepared by any of the preparation methods described above.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The chiral amino acid of the present invention is chiral threonine, the material for adjusting pH is triethylamine, and a transition metal cobalt-based chiral inorganic nanomaterial is prepared by a simple hydrothermal method, which solves the problem that the transition metal-based chiral materials are difficult to prepare. In addition, the present invention induces the twisting direction of the cobalt nanobelt by chiral threonine under high temperature and high pressure conditions, and the generated nano bow tie has chiral structures with different twisting directions, and the structure is stable and uniform without aggregation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 is a schematic flow chart of a method for preparing a chiral bowtie Co-based electrocatalyst provided in an embodiment of the present invention;
[0026] Figure 2 is a scanning electron microscope image of the sample obtained in Example 2;
[0027] Figure 3 is a scanning electron microscope image of the sample obtained in Example 3;
[0028] Figure 4 is a scanning electron microscope image of the sample obtained in Example 4;
[0029] Figure 5 is a scanning electron microscope image of the sample obtained in Example 5;
[0030] Figure 6 is a scanning electron microscope image of the sample obtained in Example 6;
[0031] Figure 7 is a scanning electron microscope image of the sample obtained in Example 7;
[0032] Figure 8 is a scanning electron microscope image of the sample obtained in Example 8;
[0033] Fig. 9 is a scanning electron microscope image of the sample obtained in Example 9;
[0034] Fig.10 is the XRD pattern of the sample prepared by adding L-Thr;
[0035] Fig.11 is the CD spectrum of the samples obtained in Example 8 and Example 9;
[0036] Fig.12 This is a graph showing the OER performance test results of the sample prepared by adding L-Thr. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.
[0038] Embodiment 1
[0039] In order to solve the problem that transition metal chiral inorganic nanomaterials are difficult to prepare, please refer to Figure 1 The present invention provides a method for preparing a chiral bowtie Co-based electrocatalyst, the preparation method comprising:
[0040] Step 1: Triethylamine is added dropwise to a first solution containing chiral threonine (Thr) to obtain a second solution.
[0041] Step 1.1, adding cobalt nitrate hexahydrate and chiral threonine into deionized water to obtain a first solution.
[0042] In this embodiment, the transition metal salt used is cobalt nitrate hexahydrate, which can induce the generation of chiral structures with different twisting directions under the action of the chiral amino acid threonine. The chiral amino acid plays an inducing role in the generation process of the chiral structure.
[0043] Optionally, the molar ratio of cobalt nitrate hexahydrate to the chiral threonine is 5:1 to 1:2. This is because when the amount of threonine is too high, the hydrothermal reaction will not produce a product, while when the amount of cobalt salt is too high, there is insufficient threonine to cooperate with it.
[0044] Step 1.2, adding triethylamine dropwise to the first solution to obtain a second solution.
[0045] Specifically, triethylamine is added dropwise to the first solution, and the mixture is stirred evenly to obtain the second solution.
[0046] Optionally, the amount of triethylamine added is 1 to 10 mL.
[0047] Preferably, the amount of triethylamine added is 5 mL.
[0048] Here, triethylamine plays a role in regulating pH on the one hand, and cobalt-based substances can only generate precipitates under alkaline conditions. On the other hand, triethylamine plays a regulatory role in the formation of the final chiral morphology. The addition of triethylamine affects the weak interaction between chiral threonine and cobalt salt, thereby affecting the growth and nucleation process of cobalt-based materials. When trying other pH regulators such as sodium hydroxide, hydrazine hydrate, ammonia water, etc., ideal chiral morphological characteristics cannot be obtained.
[0049] Step 2: Treat the second solution by hydrothermal method, and after the reaction is completed, obtain a chiral Co nano bow tie.
[0050] Specifically, the second solution is stirred by magnetic stirring, and then the second solution is transferred to a polytetrafluoroethylene liner, and then fixed with a stainless steel jacket, and then the second solution is subjected to a hydrothermal reaction at a preset temperature to obtain a chiral Co nano bow tie. The hydrothermal method can quickly carry out and complete the reaction under high temperature and high pressure conditions, and the reaction is rapid, and the reaction that is difficult to carry out at room temperature can be hydrothermally processed. The growth of the chiral structure of this embodiment is an extremely complex and lengthy process. The hydrothermal method accelerates the reaction and creates a good growth environment, so that the final chiral morphology is finally obtained by the hydrothermal method.
[0051] Optionally, the preset temperature is 160° C. to 200° C. When the temperature is lower than 160° C., it is not easy to generate a chiral structure, and when the temperature is lower than 200° C., it exceeds the bearing capacity of the hydrothermal reactor.
[0052] Optionally, the hydrothermal reaction time is 2 h to 12 h.
[0053] Step 3: Wash the chiral Co nano bow tie with anhydrous ethanol and deionized water in turn, and then dry it to obtain a dried chiral Co nano bow tie.
[0054] Because most of the chiral inorganic nanomaterials that are currently being studied involve precious metals and metals with relatively large atomic mass, and because the preparation methods and principles of transition metal chiral nanomaterials are still unclear, there is relatively little research on the construction of transition metal chiral inorganic nanomaterials. At present, the preparation of transition metal chiral inorganic nanomaterials has become a difficult problem in the industry. In the face of this technical problem, the present invention has done a lot of theoretical and experimental research. When selecting chiral amino acids and transition metal salts, only chiral threonine and cobalt nitrate hexahydrate are selected. When adjusting pH, only triethylamine is selected, and only hydrothermal method is selected as the treatment method, so that chiral nano bow ties can be generated. If other types of amino acids and transition metal salts are selected, hydrazine hydrate, ammonia water, sodium hydroxide are selected to adjust pH, and treatment methods such as room temperature precipitation method and solvent thermal method are selected, chiral nano bow ties cannot be generated. This is because, first of all, the precursor solution is chiral amino acids and metal salts dissolved in solvents with different compositions and components, and the polarity and components and composition of the solvent can affect the weak interaction (including hydrogen bond, electrostatic interaction, metal ion complexation, etc.) between the main molecule (metal salt: Co) and the guest molecule (chiral amino acid: L / D-threonine). By changing the type and concentration of chiral threonine and cobalt nitrate hexahydrate, this weak interaction can transmit the chiral signal of the chiral amino acid to the metal salt, so that it has circular dichroism. Then, the conditions such as reaction temperature, reaction time, pH value, etc. are adjusted in the manner required by the above embodiment to allow the metal chiral catalyst to crystallize and grow. Thus, this embodiment matches the most suitable reaction conditions, thereby ultimately obtaining a chiral catalyst with chiral morphological characteristics.
[0055] In summary, the chiral amino acid of the present invention is chiral threonine, the transition metal salt is cobalt nitrate hexahydrate, and the material for adjusting the pH is triethylamine. A transition metal cobalt-based chiral inorganic nanomaterial is prepared by a simple hydrothermal method, which solves the problem that transition metal-based chiral materials are difficult to prepare. In addition, the present invention induces the twisting direction of the cobalt nanobelt through chiral threonine under high temperature and high pressure conditions, and the generated nano bow tie has chiral structures with different twisting directions, and the structure is stable and uniform without aggregation. The emergence of this chiral structure improves the OER performance, which is specifically manifested in the reduction of overpotential and the lower Tafel slope.
[0056] The chiral Co nano bowtie prepared from the chiral cobalt nanomaterial prepared by the invention improves the performance of oxygen evolution in water electrolysis and can be used as an electrocatalyst for water decomposition and an electrode material for a supercapacitor.
[0057] The experimental raw materials used in the present invention are cheap and easily available, the preparation method is simple, the process is green and environmentally friendly, and there is no pollution. The chiral Co-based material finally prepared has obvious chiral characteristics and is suitable for large-scale industrial production.
[0058] Embodiment 2
[0059] Weigh 1.2 g of Co(NO 3 ) 2 6H 2 O and 1mmol of L-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0060] Embodiment 3
[0061] Weigh 1.2 g of Co(NO 3 ) 2 6H 2O and 1mmol of D-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0062] The preparation method of the present invention adopts a simple hydrothermal method, the preparation process is simple, the raw materials are easily available, and there is no pollution. The chiral β-Co(OH) 2 The chiral characteristics are obvious.
[0063] Embodiment 4
[0064] Weigh 1.2 g of Co(NO 3 ) 2 6H 2 O and 3mmol of L-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0065] Embodiment 5
[0066] Weigh 1.2 g of ECo(NO 3 ) 2 6H 2 O and 3mmol of D-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0067] Embodiment 6
[0068] Weigh 1.2 g of Co(NO 3 ) 2 6H 2 O and 5mmol of L-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0069] Embodiment 7
[0070] Weigh 1.2 g of Co(NO 3 ) 2 6H 2 O and 5mmol of D-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0071] Embodiment 8
[0072] Weigh 1.2 g of Co(NO 3 ) 2 6H 2 O and 10mmol of L-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0073] Embodiment 9
[0074] Weigh 1.2 g of Co(NO 3 ) 2 6H 2 O and 10mmol of D-Thr were dissolved in 40mL of deionized water and stirred at room temperature until completely dissolved, and then 5mL of triethylamine was dropped into the above solution and stirred until a uniform solution was formed. After the solution was magnetically stirred at 500rmp for 10min, the solution was transferred to a 100mL polytetrafluoroethylene liner, fixed with a stainless steel jacket, placed in an electric blast drying oven, and heated at 180°C for 10h. After the reactor was completely cooled, the sample was taken out and washed several times with anhydrous ethanol and deionized water respectively, and then the washed sample was placed in a vacuum drying oven at 60°C for 12h to finally obtain a dry powder sample.
[0075] See also Figures 2 to 12 , Figure 2 is a scanning electron microscope image of the sample obtained in Example 2, Figure 3 is a scanning electron microscope image of the sample obtained in Example 3, Figure 4 is a scanning electron microscope image of the sample obtained in Example 4, Figure 5 is a scanning electron microscope image of the sample obtained in Example 5, Figure 6 is a scanning electron microscope image of the sample obtained in Example 6, Figure 7 This is a scanning electron microscope image of the sample obtained in Example 7. Figure 8 is a scanning electron microscope image of the sample obtained in Example 8, Fig. 9 is a scanning electron microscope image of the sample obtained in Example 9, Fig.10 is the XRD pattern of the sample obtained by adding L-Thr, Fig.11 is the CD spectrum of the samples obtained in Example 8 and Example 9, Fig.12 It is a graph showing the OER performance test results of the sample obtained by adding L-Thr. The chiral nano bowtie material of transition metal cobalt prepared by the present invention showed obvious chiral characteristics under a scanning electron microscope, which is specifically manifested in the different twisting directions of the nanobelts. The circular dichroism spectrometer (CD) detected that the sample prepared when Thr=10mmol had good symmetry in the spectrum, which shows that the generated cobalt hydroxide material has chirality. The emergence of this chiral structure improves the OER performance, which is specifically manifested in the reduction of overpotential and the lower Tafel slope. The raw materials of this method are cheap and easy to obtain, the preparation method is simple, the process is green and environmentally friendly, and the prepared chiral structure is clearly visible, which provides new ideas and methods for the preparation of other inorganic chiral materials and has a very broad application prospect. The prepared chiral Co nano bowtie improves the performance of oxygen evolution in water electrolysis.
[0076] Embodiment 10
[0077] Based on the above embodiments, the present invention further provides a chiral bowtie Co-based electrocatalyst. The chiral bowtie Co-based electrocatalyst is prepared by the preparation method described in any one of the above embodiments.
[0078] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0079] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0080] Although the present invention is described herein in conjunction with various embodiments, in the process of implementing the claimed invention, those skilled in the art may understand and implement other variations of the disclosed embodiments by viewing the drawings, the disclosure, and the appended claims. In the claims, the word "comprising" does not exclude other components or steps, and "one" or "an" does not exclude multiple situations. A single processor or other unit may implement several functions listed in the claims. Certain measures are recorded in different dependent claims, but this does not mean that these measures cannot be combined to produce good results.
[0081] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, any modifications made without departing from the concept of the present invention should be deemed to belong to the protection scope of the present invention.
Claims
1. A method for preparing a chiral bowtie Co-based electrocatalyst, characterized in that: The preparation method comprises: adding triethylamine dropwise to the first solution containing chiral threonine to obtain a second solution; The second solution is treated by a hydrothermal method, and after the reaction is completed, a chiral Co nano bow tie is obtained, wherein triethylamine is added dropwise to the first solution containing chiral threonine to obtain a second solution, comprising: adding cobalt nitrate hexahydrate and chiral threonine into deionized water to obtain a first solution; adding triethylamine dropwise to the first solution to obtain a second solution; The molar ratio of the cobalt nitrate hexahydrate to the chiral threonine is 5:1 to 1:2; The second solution is treated by a hydrothermal method, and after the reaction is completed, a chiral Co nano bow tie is obtained, including: The second solution is stirred by magnetic stirring, and then the second solution is transferred to a polytetrafluoroethylene liner, and then fixed with a stainless steel jacket, and then the second solution is subjected to a hydrothermal reaction at a preset temperature to obtain the chiral Co nano bow tie. The second solution is subjected to a hydrothermal reaction at a preset temperature to obtain the chiral Co nano bow tie, comprising: The second solution is subjected to a hydrothermal reaction at 160° C. to 200° C. for 2 h to 12 h to obtain the chiral Co nano bow tie.
2. The method for preparing a chiral bowtie Co-based electrocatalyst according to claim 1, characterized in that: Triethylamine is added dropwise to the first solution to obtain a second solution, comprising: The triethylamine is added dropwise to the first solution, and the mixture is stirred evenly to obtain the second solution.
3. The method for preparing a chiral bowtie Co-based electrocatalyst according to claim 2, characterized in that: The amount of triethylamine added is 1-10 mL.
4. The method for preparing a chiral bowtie Co-based electrocatalyst according to claim 1, characterized in that: After the second solution is treated by a hydrothermal method and the reaction is completed to obtain a chiral Co nano bow tie, the method further includes: The chiral Co nano bow tie is washed with anhydrous ethanol and deionized water in sequence, and then dried to obtain a dried chiral Co nano bow tie.
5. A chiral bowtie Co-based electrocatalyst, characterized in that: The chiral bowtie Co-based electrocatalyst is prepared by the preparation method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Chiral cobaltosic oxide oxygen evolution electrocatalyst and preparation method thereof
CN114655996A
Chiral aryl iodine catalyst taking threonine as chiral source as well as synthesis method and application of chiral aryl iodine catalyst
CN116813659A